PKM Pemberdayaan Pelaku UMKM dibawah Naungan ASMAMI (Asosiasi Makanan dan Minuman) Kota Bontang Melalui Peningkatan Literasi Digital dan Pengembangan Media Katalog Online - Rio Jumardi; Deanita Sari; Maghfirah Maghfirah (Jurnal Informasi Pengabdian Masyarakat, 2023)
The existence of a fairly large number of MSMEs also requires competitiveness so that existing MSMEs remain competitive and can survive and develop. Apart from that, the development of digital technology also has an influence so that MSMEs can adapt. One method that can be used by MSME actors is to utilize and use information technology tools to support MSME activities, especially in marketing and promotional activities. The problem currently faced by partners is a lack of knowledge about the use of digital technology to support their MSME businesses. The results of the service team's interview with the head of ASMAMI Bontang showed that more than 50% of MSME actors under the auspices of ASMAMI Bontang did not have the skills to use digital technology. Apart from that, the infrastructure, especially technological equipment owned by MSMEs for marketing and promotional activities, is still limited. Another problem is that there are not enough MSME players to present their products in the form of attractive images to promote and advertise. The service stages consist of the preparation stage, socialization stage, implementation stage, evaluation stage and reporting stage and dissemination of service results. Community service activities in the form of empowerment to increase digital literacy and development of online catalog media at the Bontang City Food and Beverage Association have been carried out well and smoothly. Assistance activities in the form of product photo training, use of the asmamibontang.com application, introduction to digital marketing features and graphic design training using Canva received a good response from the participants who are MSMEs under the auspices of ASMAMI Bontang